2016
DOI: 10.1590/1519-6984.00314
|View full text |Cite
|
Sign up to set email alerts
|

Continuity effects on rotifers and microcrustaceans caused by the construction of a downstream reservoir in a cascade series (Iguaçu River, Brazil)

Abstract: This study evaluated changes in the community of rotifers and microcrustaceans associated with the construction of a large and dendritic reservoir in Iguaçu River (Brazil), as the last reservoir of a sequence of five cascading systems. Differences were clear between pre-filling and post-filling phases for organisms and some of environmental variables. In the pre-filling phase, the community was more homogeneous along the downstream river gradient, and spatial compartmentalization in the new reservoir was commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…The richness and Shannon-Wiener diversity index were higher in the high-water levels and also for a period of time following the reduction of the level, suggesting that the stabilization of water levels in the river and lake correlates with high richness and diversity, with a similar phenomenon occurring after a great peak in water levels. This peak can be attributed to a disturbance that generally induces variations in richness and diversity (Serafim-Júnior et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The richness and Shannon-Wiener diversity index were higher in the high-water levels and also for a period of time following the reduction of the level, suggesting that the stabilization of water levels in the river and lake correlates with high richness and diversity, with a similar phenomenon occurring after a great peak in water levels. This peak can be attributed to a disturbance that generally induces variations in richness and diversity (Serafim-Júnior et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Zooplankton organisms were collected at the subsurface of the central region using a motorized pump with velocity controlled to avoid zooplankton escaping by actively swimming away, with 600 L of water per sample filtered through a plankton net (68 μm). This method has been utilized in our study area for the last 30 years registering 541 zooplankton species, including 38 species of Trichocerca (given as an e.g., here because this genus can contain species with small body size) (Lansac‐Tôha et al, ; Serafim‐Júnior, Lansac‐Tôha, Lopes, & Perbiche‐Neves, ). The environments are shallow (<4 m deep) and water is constantly mixed, allowing to account for different zooplankters occupying different zones in the water column.…”
Section: Methodsmentioning
confidence: 99%
“…Lansac-Tôha et al, 2009;Serafim-Júnior, Lansac-Tôha, Lopes, & Perbiche-Neves, 2016). The environments are shallow (<4 m deep) and water is constantly mixed, allowing to account for different zooplankters occupying different zones in the water column.…”
mentioning
confidence: 99%
“…Thus, although our study demonstrated that run‐of‐river type dams probably have less impact than do conventional dams, there were still clear effects on zooplankton community structure during the ebb and low‐water periods, and also some effects in the other hydrological periods. Because zooplankton are adapted to the natural variation brought by the flood pulse, but not to the modifications induced by the impoundment, undesirable effects such as declines in species richness and the establishment of invasive exotic organisms (with further deleterious effects on native organisms) are expected over the longer term (Bunn & Arthington, ; Serafim‐Júnior, Lansac‐Tôha, Lopes, & Perbiche‐Neves, ).…”
Section: Conclusion and Recommendations For Monitoring Programmes In mentioning
confidence: 99%